1983
DOI: 10.1073/pnas.80.15.4861
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus DNA in Kaposi sarcoma.

Abstract: (14) by digestion with Bgl II endonuclease. The pSH6 DNA was prepared by standard methods (14). The HBV DNA fragment was purified from the excised gel piece by dissolution in sodium iodide solution, followed by addition of glass powder beads to bind the DNA (15). The DNA was eluted in 0.05 M Tris/0.001 M EDTA, pH 7.5 M. The isolated 2.8-kilobase Bgl II fragment, which spans about 80% of the HBV genome, includes a complete hepatitis B surface antigen (HBsAg) gene and most of hepatitis B core antigen (HBcAg) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Replication of the viral genome and production of the 42-nm virion in infected liver tissues are frequently observed. However, the viral DNA and proteins have also been detected in many other tissues, including kidney, spleen, pancreas, bone marrow, and circulating blood cells (16,31,41,45). Furthermore, viral genes, including both the surface and the core genes, can be expressed in cultured systems of heterologous tissue type (18,46,49).…”
Section: Methodsmentioning
confidence: 99%
“…Replication of the viral genome and production of the 42-nm virion in infected liver tissues are frequently observed. However, the viral DNA and proteins have also been detected in many other tissues, including kidney, spleen, pancreas, bone marrow, and circulating blood cells (16,31,41,45). Furthermore, viral genes, including both the surface and the core genes, can be expressed in cultured systems of heterologous tissue type (18,46,49).…”
Section: Methodsmentioning
confidence: 99%
“…In our determination, each PBMC from positive cases displayed 0.3-7.6 viral genome equivalents of HBV. These low values contrast with those in hepatic and extra-hepatic cells infected with HBV that have 1000 and 10-40 viral genome equivalents, respectively (Blum et al 1983;Siddiqui 1983). The paucity of HBV DNA in PBMC would reflect either the sensitivity of limited cells to HBV infection, or the variable population of HBV capable of infecting PBMC in each case.…”
Section: Resultsmentioning
confidence: 47%
“…Also documented in HBV DNA in tissue of Kaposi sarcoma (Siddiqui 1983) and peripheral T cells from patients with acquired immunodeficiency syndrome (Laure et al 1985 ; Noonan et al 1986). …”
mentioning
confidence: 99%
“…Integrated sequences of hepatitis B virus DNA have been identified in liver tissues derived from antigen-negative or sero-negative patients with various liver diseases [Brechot et al, 1982;Brechot et al, 19851. HBV DNA has also been found in tissues or cells other than liver [Pontisso et al, 1984;Romet-Lemonnel et al, 1983;Elfassi et al, 1984;Lie-Injo et al, 1983;Blum et al, 1983;Dejean et al, 1984a;Siddiqui, 1983;Shen et al, 1986;Gu et al, 19851. It has also been shown that leukocytes can act as a cryptic reservoir of HBV and transmit the virus to others via blood transfusion [Chong-Jin and Ling-Jeak, 19841. In Taiwan, more than 80% of the adult population has had previous HBV infection [Chen, Sung, and Lai, 1978;Sung et al, 19841.…”
Section: Introductionmentioning
confidence: 95%